Changes in the disease-specific quality of life following Dor fundoplication. A multicentre cross-sectional study. (July 2020) - Loo, Guo Hou; Rajan, Reynu; Deva Tata, Mahadevan; Ritza Kosai, Nik
Abstract: Background: Gastrooesophageal reflux disease (GERD) is a spectrum of symptoms arising from the laxity of the cardio-oesophageal junction. Anti-reflux surgery is reserved for patients with refractory GERD. Anterior partial fundoplication (Dor) is a regularly performed anti-reflux surgery in Malaysia. We intend to determine the improvement in disease-specific quality of life in our patients after surgery. Methods: A multicentre cross-sectional study was conducted to assess patients' improvement in disease-specific quality of life after Dor fundoplication. Ethics approval was obtained from our institutional review board. Patients between the ages of 18 and 65 years who underwent Dor fundoplication within the past five years were assessed using the GERD HRQL as well as the VISICK score via telephone interview. We excluded cases of revision surgery. Results: Out of 129 patients screened, 55 patients were included. We found a significant improvement in patients' GERD HRQL score with the pre-operative mean score of 28.3 ± 9.39 and 6.55 ± 8.52 post-operatively, p < 0.01.50.9% of patients reported a VISICK score of 1. However, we noticed a deterioration in the GERD HRQL and VISICK score in patients followed up four years after surgery. This consisted of 25.5% of total patients. Conclusion: Dor Fundoplication improves the overall disease-specific quality of life in patients with refractory GERD in the short term period. Recurrence of symptoms causing a deterioration in the quality of life is seen in patients followed up beyond four years of index surgery. Highlights: A multicenter cross-sectional study was conducted to assess patients' disease-specific quality of life after Dor fundoplication. The mean GERD HRQL score pre-operatively was 28.3 ± 9.39 and improved to a score of 6.55 ±8.52 post-operatively. 52.7% of patients do not require PPIs after surgery, while 23.6% still required PPI rarely (<1/week). The GERD HRQL global satisfaction score showed that 81.8% of patients were satisfied with their symptoms post-operatively. Symptom recurrence after four years and beyond may cause a deterioration in the disease-specific quality of life.